Inter-institutional cooperation management model as a patrimonial strategy: Kuntur Wasi Case (LACCEI, 2024)
Currently, many kinds of organizations have sought to generate alliances and promote projects that encourage identity in society. So, it seems to have a clearer scope of how these good practices are having a positive effect or not in local society. For this reason, a case was identified in an archaeological site, which marked a turning point in the conception of history in northern Peru, as well as in the understanding of the origin of the andean civilization in a big picture. Kuntur Wasi, an archaeological site discovered by the Japanese Archaeological Mission, has shown the world how cooperative work can emerge in local communities, and with it, stand out the participation in a model that allows archaeological sites to be configured as spaces of value for society. This research is carried out in a qualitative approach, through observation in the site and interviews with residents, whose results are evaluated and analyzed with the perspective of projecting a replica of these good practices carried out in the town of Kuntur Wasi. Finally, the main conclusions obtained from the field visit and analysis work are compiled.